ANALISIS KEMAMPUAN BERPIKIR KRITIS DAN KREATIF PADA PENYUSUNAN LAPORAN PRAKTIKUM FISIKA DASAR - Anugrahaini, Ulya Santa; Nugroho, Sunyoto Eko; Yulianto, Agus (Universitas Negeri Semarang, 2017)
Practical report as one of the written works, describes the thinking ability, especially critical and creative thinking ability. Application of critical thinking is intended to generate seports that can be understood by the reader comprehensively. The application of creative thinking ability is used to bring up the aesthetic results of lab reports. This study aimed to analize the critical and creative thinking ability and patterns in the preparation of the basic physics lab results. The research data applying cocument analysis, questionnaire, and confirmed by an interview given to students of Physical Education. Grounded theoriy is used to analize this study. The results showed that students critical thinking ability tha are in medium and high category whose are different pattern. Differences in pattern between students ability to think high and medium category critically is located on the caracteristics of those key issue on the basic components of the theory that clarivy the terms of physics (definition, examples, and background), clarivying the mathematical equations used to provide meaning and reveal facts that are pailored to the theory on the data analized component. Diffrences capable of creative thinking ability of students high and medium categories is located in the birth of new ideas coming from students thinking practitioner in the preaparation of the component of interest, and detailing and object so that it is more valuable to describe the tools anda materials used for practical implementation.